Positive electrode active material for lithium ion secondary battery, method for producing positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery
The development of a lithium transition metal composite oxide with controlled elemental proportions and particle sizes enhances the cycle characteristics and battery capacity of lithium-ion secondary batteries by maintaining lithium insertion and reducing nickel occupancy in the Li site.
Patent Information
- Application Number
- JP2023123253
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
Lithium-ion secondary batteries require further improvements in cycle characteristics, particularly in the positive electrode active materials, to enhance their performance in various applications.
A positive electrode active material for lithium-ion secondary batteries is developed, comprising lithium transition metal composite oxides with a layered rock salt type structure, where the proportion of elements other than Li in the Li site (3b site) is between 2% and 8%, and the composition is represented by Li 1-x NiO 2+α with 0.02≦x≦0.08 and -0.1≦α≦0.1, and the average particle diameter of primary particles is 20 nm to 250 nm.
The proposed active material improves cycle characteristics and battery capacity by preventing nickel from occupying lithium sites during charging and discharging, thereby maintaining lithium insertion and reducing initial capacity loss, while ensuring sufficient lithium for charging and discharging reactions.
Smart Images

Figure 2025019576000002 
Figure 2025019576000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery, a method for producing a positive electrode active material for a lithium ion secondary battery, and a lithium ion secondary battery. [Background technology]
[0002] 2. Description of the Related Art In recent years, with the widespread use of portable electronic devices such as mobile phone terminals and notebook computers, there has been a strong demand for the development of small, lightweight non-aqueous electrolyte secondary batteries that have high energy density and durability.
[0003] Non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries are available as secondary batteries that meet these requirements. Lithium ion secondary batteries, which use lithium metal composite oxides with layered or spinel-type crystal structures as the positive electrode active material, can obtain high voltages of about 4V, and are therefore being put to practical use as batteries with high energy density.
[0004] Lithium metal composite oxides include lithium cobalt composite oxide (LiCoO2), which is relatively easy to synthesize, lithium nickel composite oxide (LiNiO2), which uses nickel, which is cheaper than cobalt, and lithium nickel cobalt manganese composite oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), lithium manganese composite oxide (LiMn2O4), lithium nickel manganese composite oxide (LiNi 0.5 Mn 0.5 O2) have been proposed.
[0005] In recent years, there has been a demand for further improvements in the battery characteristics of lithium-ion secondary batteries, and various studies have been conducted.
[0006] For example, Patent Documents 1 to 5 disclose that by controlling the particle characteristics of a lithium composite oxide, it is possible to improve the cycle characteristics, which is the capacity retention rate when a lithium ion secondary battery using the lithium composite oxide is repeatedly charged and discharged. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2001-243949 A [Patent Document 2] JP 2004-355824 A [Patent Document 3] JP 2017-188444 A [Patent Document 4] JP 2017-188445 A [Patent Document 5] International Publication No. 2017 / 169129 Summary of the Invention [Problem to be solved by the invention]
[0008] However, as described above, lithium ion secondary batteries are being used in various applications, and further improvements in performance are being demanded. For this reason, there is also a demand for improving the performance, such as cycle characteristics, of positive electrode active materials for lithium ion secondary batteries when used in lithium ion secondary batteries by a method different from the conventional method.
[0009] In view of the problems associated with the above-mentioned conventional techniques, an object of one aspect of the present invention is to provide a positive electrode active material for lithium ion secondary batteries that can improve cycle characteristics when used in lithium ion secondary batteries. [Means for solving the problem]
[0010] In order to solve the above problem, according to one aspect of the present invention, A positive electrode active material for a lithium ion secondary battery, comprising secondary particles in which a plurality of primary particles are aggregated together, The lithium transition metal composite oxide has a layered rock salt structure, In the crystal structure of the lithium transition metal composite oxide, the ratio of elements other than Li to the Li site (3b site) is 2% or more and 8% or less, The present invention provides a positive electrode active material for a lithium ion secondary battery, the composition of which is represented by the following general formula (1):
[0011] General formula (1): Li 1-x NiO 2+α (where 0.02≦x≦0.08 and -0.1≦α≦0.1) Effect of the Invention
[0012] According to one embodiment of the present invention, it is possible to provide a positive electrode active material for a lithium ion secondary battery that can improve cycle characteristics when used in a lithium ion secondary battery. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 shows a flow of a method for producing a positive electrode active material for a lithium ion secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, the form for carrying out the present invention will be described with reference to the drawings. However, the present invention is not limited to the following embodiment, and various modifications and substitutions can be made to the following embodiment without departing from the scope of the present invention. [Positive electrode active material for lithium-ion secondary batteries] Hereinafter, the positive electrode active material for a lithium ion secondary battery (hereinafter, also simply referred to as "positive electrode active material") of this embodiment will be described. (1) Positive electrode active material The positive electrode active material of the present embodiment contains a lithium transition metal composite oxide. The positive electrode active material of the present embodiment may be composed only of a lithium transition metal composite oxide, but even in this case, it does not exclude the inclusion of inevitable impurities that are mixed in during the manufacturing process or the like.
[0015] The lithium transition metal composite oxide can have a layered rock salt structure. (1-1) Particle morphology The particle shape of the positive electrode active material of this embodiment is not particularly limited, but the positive electrode active material of this embodiment may contain secondary particles in which a plurality of primary particles are aggregated together. Therefore, the positive electrode active material of this embodiment may be composed only of secondary particles, or may contain primary particles that exist independently without aggregation in addition to the secondary particles.
[0016] The particles of the positive electrode active material of this embodiment can contain particles of a lithium transition metal composite oxide, and may be composed of particles of a lithium transition metal composite oxide.
[0017] The particle morphology of the positive electrode active material of this embodiment can be roughly confirmed by a scanning electron microscope (SEM) observation image (hereinafter also referred to as "SEM image") of the particle, but the image may lack accuracy. In the positive electrode active material of this embodiment, it is preferable to process the cross section of the particle and use the SEM image to determine the presence or absence of primary particles and secondary particles.
[0018] Specifically, for example, it is preferable to embed particles of the positive electrode active material in a resin, and then perform cross-section polishing (CP) processing or the like to make the cross-section of the particles observable, and then observe the SEM image to determine the presence or absence of primary particles and secondary particles. For the determination, it is preferable to perform the above evaluation on 50 or more particles. There is no particular upper limit on the number of particles to be evaluated, but it is preferable to perform the evaluation on 200 or less particles in consideration of the productivity of the evaluation.
[0019] In addition, the above particle cross-sections can be confirmed using band contrast in the electron backscatter diffraction (hereinafter also referred to as "EBSD") method, or when using a focused ion beam (FIB) processing device for cross-section processing, using the attached scanning ion microscope (SIM) observation image. (1-2) Composition of lithium transition metal composite oxide The lithium transition metal composite oxide can be composed of lithium (Li), nickel (Ni), and oxygen (O). Therefore, the composition of the lithium transition metal composite oxide is represented by the following general formula (1).
[0020] General formula (1): Li 1-x NiO 2+α In the above general formula, x and y preferably satisfy 0.02≦x≦0.08 and −0.1≦α≦0.1.
[0021] In lithium nickel oxide represented by LiNiO2, the stoichiometric ratio of lithium element to nickel element is 1.00. In contrast, in the above general formula (1) of the lithium transition metal composite oxide contained in the positive electrode active material of this embodiment, the substance amount ratio of lithium element to nickel element is represented by 1-x. In the above general formula of the lithium transition metal composite oxide, the value of x in 1-x indicating the substance amount ratio of lithium element to nickel element corresponds to the amount of deficiency from the stoichiometric ratio of lithium element. In the lithium transition metal composite oxide contained in the positive electrode active material of this embodiment, x is preferably 0.02≦x≦0.08. That is, it is preferable that the substance amount ratio of lithium element to nickel element in the lithium transition metal composite oxide contained in the positive electrode active material of this embodiment is 0.98 or less and has a deficiency.
[0022] By setting the value of x, which corresponds to the amount of deficiency from the stoichiometric ratio of lithium element, to 0.02 or more and 0.08 or less to form a lithium transition metal composite oxide having a deficiency of lithium element, the amount of lithium compound attached to the particle surface of the positive electrode active material of this embodiment, i.e., the amount of alkali, can be suppressed. Therefore, when the positive electrode active material of this embodiment is applied to a lithium ion secondary battery (hereinafter also referred to as "secondary battery"), gas generation during the battery reaction can be suppressed.
[0023] Furthermore, by setting the value of x, which corresponds to the amount of deficiency from the stoichiometric ratio of lithium element, to 0.02 or more and 0.08 or less, when the positive electrode active material of this embodiment is applied to a secondary battery, the cycle characteristics can be improved.
[0024] The composition of the lithium nickel composite oxide can be measured by quantitative analysis using inductively coupled plasma (ICP) emission spectrometry. (1-3) Proportion of elements other than Li in the Li site (3b site) In the lithium transition metal composite oxide contained in the positive electrode active material according to this embodiment, in the crystal structure of the lithium transition metal composite oxide, the proportion of elements other than Li in the Li sites (3b sites) is preferably 2% or more and 8% or less, more preferably 2% or more and 6% or less.
[0025] The ratio of elements other than Li to the Li site (3b site) refers to the ratio of nickel elements to the Li site (3b site). The ratio of elements other than Li to the Li site (3b site) can be obtained by analyzing the powder X-ray diffraction pattern measured by the powder X-ray diffraction method using the Rietveld method. When analyzing using the Rietveld method, a layered rock salt structure, which is a crystal structure of a lithium transition metal composite oxide, can be used as the crystal structure.
[0026] When a secondary battery is repeatedly charged and discharged, lithium is repeatedly inserted and removed between the layers of the lithium transition metal composite oxide. However, when a secondary battery using a conventional positive electrode active material is repeatedly charged and discharged, nickel may move and occupy some of the voids that are generated by the lithium removal. It is believed that the cycle characteristics are reduced because lithium is no longer inserted into the sites occupied by nickel.
[0027] In contrast, in the lithium transition metal composite oxide contained in the positive electrode active material of this embodiment, the ratio of elements other than Li to the Li site (3b site) is 2% or more. It is believed that by inserting nickel into the Li site in advance in this way, it is possible to suppress the insertion of nickel into the site generated by the desorption of lithium during charging. Therefore, it is believed that the decrease in battery capacity when charging and discharging are repeated can be suppressed and the cycle characteristics can be improved.
[0028] In addition, by keeping the ratio of elements other than Li in the Li site (3b site) to 8% or less, the decrease in initial capacity can be suppressed, ensuring a sufficient amount of lithium that contributes to charging and discharging, suppressing reaction resistance, and sufficiently increasing battery capacity and output. (1-4) Average particle size of primary particles In the positive electrode active material of this embodiment, the average particle size of the primary particles is preferably 20 nm or more and 250 nm or less, and more preferably 20 nm or more and 150 nm or less.
[0029] By making the average particle diameter of the primary particles of the positive electrode active material of this embodiment 20 nm or more, it means that the size of the primary particles contained in the positive electrode active material of this embodiment and the crystallites constituting the primary particles can be made sufficiently large. Therefore, the crystallinity of the lithium transition metal composite oxide contained in the positive electrode active material can be increased, and when the positive electrode active material of this embodiment is applied to a secondary battery, the battery capacity can be increased, and a secondary battery excellent in battery capacity and cycle characteristics can be obtained.
[0030] However, even if the average particle size of the primary particles of the positive electrode active material of this embodiment is excessively large, the effect of increasing the battery capacity is saturated, so the average primary particle size of the lithium nickel composite oxide is preferably 250 nm or less.
[0031] The average particle size of the primary particles of the positive electrode active material is determined by selecting primary particles of the positive electrode active material that can be observed in their entirety using a scanning electron microscope (SEM), measuring their major axis lengths, and averaging them. When calculating the average particle size of the primary particles, the number of primary particles to be evaluated is not particularly limited.
[0032] For example, when the positive electrode active material contains secondary particles, it is preferable to select 10 to 20 secondary particles, select primary particles from each of the selected secondary particles, and then select a total of 20 to 30 primary particles, and measure the major axis length of the selected primary particles.
[0033] In addition, when the positive electrode active material contains a single primary particle that does not constitute a secondary particle, it is preferable to evaluate 5 or more primary particles of the positive electrode active material. There is no particular upper limit on the number of primary particles to be evaluated, but it is preferable to evaluate, for example, 20 or less.
[0034] When the positive electrode active material contains only secondary particles, the above number of secondary particles can be selected from the secondary particles, and the above number of primary particles can be selected in total from each secondary particle. The lengths of the major axes of the selected primary particles can then be measured, and the average value can be used as the average particle size of the primary particles of the positive electrode active material.
[0035] When the positive electrode active material contains both secondary particles and single primary particles, the above-mentioned number of primary particles can be selected for each of the selected number of secondary particles and the single primary particles. Then, the lengths of the major axes of all the selected primary particles can be measured, and the average value can be regarded as the average particle size of the primary particles of the positive electrode active material.
[0036] By setting the average particle size of the primary particles of the positive electrode active material within the above range, when the positive electrode active material is applied to a secondary battery, it is possible to particularly improve both the battery capacity and the cycle characteristics, and to achieve a balance between them. [Method of manufacturing positive electrode active material for lithium ion secondary batteries] The method for producing the positive electrode active material for a lithium ion secondary battery is not particularly limited as long as the positive electrode active material having the above characteristics can be obtained. Hereinafter, an example of the method for producing the positive electrode active material according to the present embodiment will be described.
[0037] As described above, according to the method for producing a positive electrode active material of this embodiment, the positive electrode active material already described can be produced, and therefore some of the matters already described will not be described again.
[0038] The method for producing a positive electrode active material of this embodiment can be carried out, for example, according to flow 10 shown in Fig. 1. That is, the method for producing a positive electrode active material of this embodiment can include a mixing step (S1) and a firing step (S2).
[0039] In the mixing step (S1), a lithium mixture can be obtained by mixing a nickel compound, which is at least one selected from nickel hydroxide and nickel oxide, with a lithium compound. In this case, it is preferable to mix so that the atomic ratio of lithium atoms to nickel atoms in the resulting lithium mixture is 0.92 to 0.98.
[0040] In the calcination step (S2), the lithium mixture is calcined to produce a positive electrode active material. In the calcination step, the temperature is preferably increased at a rate of 2° C. / min or less and calcined at a temperature of 600° C. or more and 700° C. or less.
[0041] An example of the configuration of each step will be described below. (1) Mixing process (S1) In the mixing step (S1), as described above, a nickel compound, which is one or more types selected from nickel hydroxide and nickel oxide, is mixed with a lithium compound to obtain a lithium mixture.
[0042] The nickel compound and the lithium compound can be added, for example, in the form of powder (solid phase) and mixed in. Hereinafter, each of the raw materials to be subjected to the mixing step will be described. (1-1) Raw materials (Nickel compounds) The nickel compound used in the mixing step (S1) can be obtained by a known method.
[0043] The nickel compound may be nickel hydroxide or nickel oxide. The nickel compound may be a mixture of nickel hydroxide and nickel oxide. Examples of a method for producing nickel hydroxide include a method of neutralization crystallization using an aqueous solution of a nickel salt and an alkaline solution. In addition, a part or all of the nickel hydroxide may be converted into nickel oxide by heat treating the nickel hydroxide to remove moisture from the nickel hydroxide. (Lithium compounds) The lithium compound is not particularly limited, and any known compound containing lithium can be used, for example, one or more selected from lithium carbonate, lithium hydroxide, and lithium nitrate. The lithium compound may be a mixture of two or more compounds selected from the above compounds.
[0044] The lithium compound is preferably one or more selected from lithium carbonate and lithium hydroxide from the viewpoints of being less affected by residual impurities and dissolving at the firing temperature, and more preferably lithium hydroxide from the viewpoint of obtaining a lithium transition metal composite oxide having particularly high crystallinity. (1-2) Mixing method The method for mixing the nickel compound and the lithium compound is not particularly limited. It is preferable to mix these particles sufficiently so that the particles are not destroyed.
[0045] The nickel compound and the lithium compound can be mixed, for example, using a general mixer, such as a shaker mixer, a Loedige mixer, a Julia mixer, a V blender, etc. If the mixing is insufficient, the mass ratio (Li / Ni) of lithium (Li) and nickel (Ni) varies between individual particles of the positive electrode active material, which can cause problems such as insufficient battery characteristics being obtained, and therefore it is preferable to mix them sufficiently. (1-3) Mixing ratio The lithium compounds are preferably mixed so that the ratio (Li / Ni) of the number of lithium atoms (Li) to the number of nickel atoms (Ni) in the lithium mixture obtained in the mixing step is 0.92 or more and 0.98 or less. In other words, it is preferable to mix so that the Li / Ni in the lithium mixture is the same as the Li / Ni in the obtained fired product. This is because the ratio of the amounts of substances of each element of lithium and nickel does not change before and after the firing step (S2), so the Li / Ni in the lithium mixture in the mixing step (S1) becomes equal to the Li / Ni in the fired product. The content (ratio) of the elements in the lithium mixture is almost maintained in the lithium transition metal composite oxide. (2) Firing process (S2) The firing step (S2) is a step of firing the lithium mixture obtained in the mixing step (S1) to obtain a fired product containing a lithium transition metal composite oxide. When the lithium mixture is fired, the lithium in the lithium compound diffuses into the nickel compound to form a lithium transition metal composite oxide. The lithium compound melts at the firing temperature and permeates into the nickel compound to form a fired product of the lithium transition metal composite oxide.
[0046] The firing conditions in the firing step (S2) are not particularly limited, and can be selected so that the lithium transition metal composite oxide has a desired composition and the properties such as the ratio of elements other than Li in the Li site (3b site) are within the desired range. Preferred examples of the firing conditions are described below. (atmosphere) The firing atmosphere is preferably an oxidizing atmosphere. The oxidizing atmosphere preferably has an oxygen concentration of 60% by volume or more, more preferably an oxygen concentration of 80% by volume or more, and even more preferably an oxygen concentration of 85% by volume or more. The oxidizing atmosphere can also be an oxygen atmosphere, so the oxygen concentration can be 100% by volume or less.
[0047] In this specification, the firing atmosphere refers to the gas supplied to the firing furnace. (Firing temperature) The firing is preferably carried out at a temperature of 600°C or higher and 700°C or lower, more preferably at a temperature of 610°C or higher and 685°C or lower, and even more preferably at a temperature of 625°C or higher and 675°C or lower.
[0048] The lithium mixture can be fired by increasing the temperature from room temperature to the firing temperature and then decreasing the temperature to room temperature.
[0049] The rate of temperature rise to the above-mentioned firing temperature is preferably 2° C. / min or less, and more preferably 0.1° C. / min or more and 2° C. / min or less.
[0050] By setting the temperature rise rate at 2° C. / s or less, the reaction in the lithium mixture can proceed uniformly, and the crystal growth of the lithium transition metal composite oxide can be promoted.
[0051] The time for which the firing temperature is maintained is not particularly limited, but is preferably 5 hours or more, and more preferably 10 hours or more and 48 hours or less.
[0052] By firing a predetermined lithium mixture according to the above temperature pattern, the proportion of elements other than Li at the Li site (3b site) of the lithium transition metal composite oxide can be easily adjusted to fall within the above-mentioned range.
[0053] In addition, the firing conditions such as the suitable firing temperature may change in order to set the ratio of elements other than Li in the Li site (3b site) within a desired range depending on the content ratio of lithium and nickel in the target composition of the lithium transition metal composite oxide. Therefore, it is preferable to select the optimal firing temperature within the above temperature range depending on the target composition, and to select temperature conditions such as the heating rate and holding time.
[0054] The method for producing a positive electrode active material according to the present embodiment may include any step other than the mixing step and the firing step. (3) Crushing process The fired product obtained in the firing step (S2) can also be used as the positive electrode active material of this embodiment. However, the fired product obtained after the firing step (S2) may have coarse particles formed due to weak sintering or aggregation, although sintering between particles is suppressed. In such a case, the method for producing the positive electrode active material of this embodiment can also include a crushing step of crushing the fired product. By crushing the fired product, the sintering and aggregation can be eliminated, and the particle size distribution can be adjusted. (4) Crushing process The method for producing a positive electrode active material of this embodiment may also include a crushing step of crushing the fired product or crushed powder after the firing step (S2) or after the crushing step.
[0055] After the crushing or pulverizing step, sieving may be carried out to select particles of a desired particle size. (5)Water washing process The method for producing a positive electrode active material of this embodiment may also include a water washing step of washing the fired product obtained in the firing step (S2) with water.
[0056] By carrying out the water washing step, excess lithium remaining on the particle surfaces of the positive electrode active material can be removed.
[0057] In the water-washing step, the fired product can be mixed with water to form a slurry and then washed with water (slurrying step).
[0058] The water used in forming a slurry in the water washing step is not particularly limited, but for example, water having an electrical conductivity of preferably less than 10 μS / cm, more preferably 1 μS / cm or less can be used.
[0059] It is preferable to stir the prepared slurry during washing with water.
[0060] In the water washing step, after the slurry is made, the slurry is subjected to solid-liquid separation, i.e., filtration and dehydration to obtain water-washed powder (solid-liquid separation step). The apparatus used for filtration and dehydration is not particularly limited, and for example, a centrifugal separation type or a filter press type solid-liquid separation apparatus can be used.
[0061] In the water washing step, the water-washed powder containing water obtained after solid-liquid separation is preferably dried (drying step). The drying conditions are not particularly limited, but it is preferable to perform the drying at a temperature of 100° C. or higher and 350° C. or lower in an oxidizing atmosphere or a vacuum atmosphere.
[0062] In the mixing step, a lithium transition metal composite oxide with Li / Me of 0.92 to 0.98 can be obtained by washing the fired product produced under the above-mentioned conditions of Li / Ni of 1.00 or more with water. However, according to the study by the inventors of the present invention, in the above case, a positive electrode active material that satisfies the requirements of the positive electrode active material of this embodiment regarding the ratio of elements other than Li in the Li site (3b site) cannot be obtained, and the effect of the positive electrode active material of this embodiment cannot be obtained. [Lithium-ion secondary battery] The lithium ion secondary battery of this embodiment includes at least a positive electrode, a negative electrode, and a non-aqueous electrolyte, and the positive electrode can include the above-described positive electrode active material for lithium ion secondary batteries.
[0063] Hereinafter, one configuration example of the secondary battery of this embodiment will be described for each component. The secondary battery of this embodiment includes, for example, a positive electrode, a negative electrode, and a non-aqueous electrolyte, and is composed of the same components as a general lithium-ion secondary battery. Note that the embodiment described below is merely an example, and the lithium-ion secondary battery of this embodiment can be embodied in various forms that have been modified and improved based on the knowledge of those skilled in the art, including the following embodiment. In addition, the secondary battery is not particularly limited in its use. (positive electrode) The positive electrode of the secondary battery of this embodiment can contain the positive electrode active material described above.
[0064] An example of a method for manufacturing a positive electrode is described below. First, the positive electrode active material (powder), conductive agent, and binder are mixed to prepare a positive electrode mixture, and activated carbon and a solvent for viscosity adjustment, etc. are added as necessary, and the mixture is kneaded to prepare a positive electrode mixture paste.
[0065] The mixing ratio of each material in the positive electrode mixture is a factor that determines the performance of the lithium ion secondary battery, and can be adjusted depending on the application. The mixing ratio of the materials can be the same as that of the positive electrode of a known lithium ion secondary battery, and for example, when the total mass of the solid content of the positive electrode mixture excluding the solvent is taken as 100 mass%, the positive electrode active material can be contained in a ratio of 60 mass% to 95 mass%, the conductive agent can be contained in a ratio of 1 mass% to 20 mass%, and the binder can be contained in a ratio of 1 mass% to 20 mass%.
[0066] The obtained positive electrode mixture paste is applied to the surface of a current collector made of, for example, aluminum foil, and dried to remove the solvent, thereby producing a sheet-like positive electrode. If necessary, pressure can be applied by a roll press or the like to increase the electrode density. The sheet-like positive electrode thus obtained can be cut to an appropriate size according to the desired battery and used for the production of the battery.
[0067] As the conductive agent, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.) and carbon black-based materials such as acetylene black and Ketjen Black (registered trademark) can be used.
[0068] The binder serves to bind the active material particles together, and may be, for example, one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose-based resin, polyacrylic acid, etc.
[0069] If necessary, a solvent for dispersing the positive electrode active material, conductive agent, etc. and dissolving the binder can be added to the positive electrode mixture. Specifically, an organic solvent such as N-methyl-2-pyrrolidone can be used as the solvent. Activated carbon can also be added to the positive electrode mixture to increase the electric double layer capacity.
[0070] The method for producing the positive electrode is not limited to the above-mentioned example, and other methods may be used. For example, the positive electrode may be produced by pressing the positive electrode mixture and then drying it in a vacuum atmosphere. (Negative electrode) The negative electrode may be made of metallic lithium, a lithium alloy, etc. Alternatively, the negative electrode may be made by mixing a binder with a negative electrode active material capable of absorbing and desorbing lithium ions, adding an appropriate solvent to make a paste-like negative electrode mixture, applying the mixture to the surface of a metal foil current collector such as copper, drying it, and compressing it to increase the electrode density as necessary.
[0071] As the negative electrode active material, for example, natural graphite, artificial graphite, sintered organic compounds such as phenol resin, and powder of carbon material such as coke can be used. In this case, as with the positive electrode, fluorine-containing resin such as PVDF can be used as the negative electrode binder, and an organic solvent such as N-methyl-2-pyrrolidone can be used as the solvent for dispersing these active materials and binders. (Separator) A separator may be sandwiched between the positive electrode and the negative electrode as necessary. The separator separates the positive electrode and the negative electrode and holds the electrolyte, and any known separator may be used, such as a thin membrane made of polyethylene or polypropylene having many minute pores. (Non-aqueous electrolyte) As the non-aqueous electrolyte, for example, a non-aqueous electrolytic solution can be used.
[0072] As the non-aqueous electrolyte, for example, a solution in which a lithium salt as a supporting salt is dissolved in an organic solvent can be used. Alternatively, as the non-aqueous electrolyte, a solution in which a lithium salt is dissolved in an ionic liquid can be used. Note that the ionic liquid refers to a salt that is composed of cations and anions other than lithium ions and is liquid even at room temperature.
[0073] The organic solvent may be one selected from cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate; ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane; sulfur compounds such as ethyl methyl sulfone and butane sultone; and phosphorus compounds such as triethyl phosphate and trioctyl phosphate. Two or more of these organic solvents may be used in combination.
[0074] The supporting salt may be LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, or a composite salt thereof. Furthermore, the non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant, and the like.
[0075] The non-aqueous electrolyte may be a solid electrolyte. The solid electrolyte has a property of being able to withstand high voltage. Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes.
[0076] Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes.
[0077] The oxide-based solid electrolyte is not particularly limited, and for example, an oxide-based solid electrolyte containing oxygen (O) and having lithium ion conductivity and electronic insulation can be suitably used. Examples of the oxide-based solid electrolyte include lithium phosphate (Li3PO4), Li3PO4N X , LiBON X , LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≦X≦1), Li 1+X Al X Ge 2-X (PO4)3(0≦X≦1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3(0≦X≦2 / 3), Li5La3Ta2O 12 , Li7La3Zr2O 12 , Li6BaLa2Ta2O 12 , Li 3.6 S 0.6 P 0.4 One or more types selected from O4, etc. can be used.
[0078] The sulfide-based solid electrolyte is not particularly limited, and for example, one containing sulfur (S) and having lithium ion conductivity and electronic insulation can be suitably used. For example, the sulfide-based solid electrolyte can be one or more selected from Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc.
[0079] As the inorganic solid electrolyte, materials other than those mentioned above may be used, for example, Li3N, LiI, Li3N-LiI-LiOH, etc. may be used.
[0080] The organic solid electrolyte is not particularly limited as long as it is a polymer compound exhibiting ion conductivity, and examples of the organic solid electrolyte that can be used include polyethylene oxide, polypropylene oxide, copolymers thereof, etc. The organic solid electrolyte may also contain a supporting salt (lithium salt). (Shape and structure of secondary battery) The lithium ion secondary battery of the present embodiment described above can be made into various shapes such as a cylindrical shape or a laminated shape. Regardless of the shape, if the secondary battery of the present embodiment uses a non-aqueous electrolyte as the non-aqueous electrolyte, the positive electrode and the negative electrode can be laminated through a separator to form an electrode body, and the obtained electrode body can be impregnated with the non-aqueous electrolyte. Then, the positive electrode current collector and the positive electrode terminal leading to the outside, and the negative electrode current collector and the negative electrode terminal leading to the outside can be connected using a current collecting lead or the like, and the structure can be sealed in a battery case.
[0081] As described above, the secondary battery of the present embodiment is not limited to a form using a non-aqueous electrolyte solution as a non-aqueous electrolyte, and may be, for example, a secondary battery using a solid non-aqueous electrolyte, i.e., an all-solid-state battery. When making an all-solid-state battery, the configuration other than the positive electrode active material may be changed as necessary.
[0082] The secondary battery of this embodiment can be used for various purposes. Since the secondary battery of this embodiment can be a high-capacity, high-output secondary battery, it is suitable for use as a power source for small portable electronic devices (such as notebook personal computers and mobile phone terminals) that always require high capacity, and is also suitable as a power source for electric vehicles that require high output.
[0083] In addition, the secondary battery of this embodiment can be made compact and have high output, making it suitable as a power source for electric vehicles that are limited in installation space. The secondary battery of this embodiment can be used not only as a power source for electric vehicles that are driven purely by electrical energy, but also as a power source for so-called hybrid vehicles that are used in conjunction with combustion engines such as gasoline engines and diesel engines. EXAMPLES
[0084] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0085] First, the evaluation methods of the positive electrode active materials and secondary batteries obtained in the following Examples and Comparative Examples will be described. (Evaluation of Positive Electrode Active Material) The obtained positive electrode active material was evaluated as follows.
[0086] (a) Evaluation of composition The composition of the positive electrode active material was analyzed by ICP emission spectrometry. The evaluation results are shown in the "Composition" column of Table 1.
[0087] (b) Proportion of elements other than Li in the Li site (3b site) For the positive electrode active materials prepared in the following Examples and Comparative Examples, X-ray diffraction patterns were measured using an X-ray diffractometer (XRD) X'PertPRO (manufactured by Spectris, Inc.) The X-ray diffraction patterns were measured using CuKα radiation.
[0088] From the obtained X-ray diffraction patterns, it was confirmed that the lithium transition metal composite oxides contained in the positive electrode active materials obtained in the following Examples 1 to 7 and Comparative Examples 1 to 3 had a layered rock salt structure.
[0089] The obtained X-ray diffraction pattern was subjected to Rietveld analysis using the crystal structure analysis software RIETAN. In this case, the space group was set to R-3m, and lithium and mixed nickel (nickel in the lithium site) were set as the chemical species in the 3b site, and nickel was set as the chemical species in the 3a site. After refining the scale factor, lattice constant, and global parameters, the site occupancy rate and atomic coordinates were refined. The site occupancy rate of nickel in the obtained lithium site (3b site) was calculated, and the results are shown in the column of "Proportion of elements other than Li in the Li site (3b site)" in Table 1.
[0090] (c) Average particle size of primary particles In the SEM observation image of the lithium nickel composite oxide particles, 15 secondary particles that could be observed in their entirety by image analysis were selected, and primary particles were selected from each selected secondary particle. At this time, a total of 30 primary particles were selected. The major axis lengths of the selected primary particles were then measured, and the average value was taken as the average particle size of the primary particles.
[0091] The evaluation results are shown in Table 1 in the column "Average particle size of primary particles." (Production and evaluation of lithium-ion secondary batteries) (a) Preparation of coin-type battery Coin type batteries were produced using the positive electrode active materials produced in the following Examples and Comparative Examples.
[0092] Specifically, 0.170 g of the positive electrode active material obtained in the following Examples and Comparative Examples was weighed out in a glove box under an argon atmosphere. The weighed positive electrode active material was then placed in a container together with 0.010 g of acetylene black, 0.250 g of polyvinylidene fluoride (PVDF) solution (8% solution manufactured by Kureha) and 70 μL of N-methyl-2-pyrrolidone (NMP), and mixed with a stirrer (AR-100 manufactured by Thinky).
[0093] The slurry obtained by stirring was applied to an aluminum foil and vacuum dried at room temperature for 2 hours, and then vacuum dried at 120°C for 2 hours to obtain an electrode.
[0094] The obtained electrode was punched out to a diameter of 10 mm, the weight was measured, and this was used as a positive electrode.
[0095] Metallic lithium was used as the negative electrode, and a polyethylene (PE) porous film was used as the separator, and the positive electrode, separator, and negative electrode were laminated in that order. The laminate of the positive electrode, separator, and negative electrode was impregnated with an electrolyte and sealed between the positive electrode can and the negative electrode can. A gasket was placed between the positive electrode can and the negative electrode can, and the two components were fixed in place to restrict relative movement so as to maintain a non-contact state, i.e., an electrically insulated state.
[0096] The electrolyte used was a 3:7 mixture (volume ratio) of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiPF6 as the supporting electrolyte.
[0097] The coin-type battery was fabricated in a dry room with a dew point controlled at -60°C.
[0098] (b) Evaluation of discharge capacity and cycle characteristics The capacity retention rate, which indicates cycle characteristics, was evaluated by measuring the capacity retention rate after 100 charge / discharge cycles for a coin-type battery.
[0099] Specifically, a current of 10 mA / g was applied to the coin battery, and the battery was charged to a cutoff voltage of 4.5 V and then discharged to a cutoff voltage of 2.5 V. This cycle was repeated 100 times. The capacity retention rate, which is the ratio of the discharge capacity at the 100th cycle after conditioning to the discharge capacity at the 1st cycle, was calculated and evaluated.
[0100] The discharge capacity at the first cycle is shown in the "Initial capacity" column of Table 1, and the capacity retention rate is shown in the "Capacity retention rate" column of Table 1. (Production conditions of positive electrode active material) [Example 1] Nickel hydroxide and lithium hydroxide monohydrate, both of which were obtained by a known method, were mixed to prepare a lithium mixture (mixing step).
[0101] In the mixing process, nickel hydroxide and lithium hydroxide monohydrate were thoroughly mixed using a shaker mixer (Willi & Bachofen (WAB), model: TURBULA Type T2C) to prepare a raw material mixture.
[0102] In the mixing step, the raw materials were weighed and mixed so that the ratio (Li / Ni) of the number of lithium atoms (Li) to the number of nickel atoms (Ni) in the resulting lithium mixture was 0.96. The nickel oxide was obtained by heat-treating nickel hydroxide obtained by a crystallization method.
[0103] During the firing step, oxygen was supplied into the furnace, and the lithium mixture was fired in an oxygen atmosphere (firing step).
[0104] The firing temperature was increased to 650° C. at a rate of 2° C. / min, and the firing temperature was maintained at 650° C. for 12 hours. After maintaining the firing temperature, the firing temperature was cooled to room temperature.
[0105] The fired lithium transition metal composite oxide was crushed (crushing step) to obtain a positive electrode active material made of lithium transition metal composite oxide particles.
[0106] Observation of the obtained positive electrode active material by SEM confirmed that the positive electrode active material was composed of secondary particles in which a plurality of primary particles were aggregated together. Note that, in the following other examples, it was also confirmed that the positive electrode active material was composed of secondary particles in which primary particles were aggregated together.
[0107] Other evaluation results are shown in Table 1.
[0108] The positive electrode active material thus obtained was used to fabricate the coin-type battery described above, which was then evaluated. The evaluation results are shown in Table 1. [Example 2] In the mixing step, the mixing ratio of lithium hydroxide monohydrate and nickel hydroxide was changed so that the ratio (Li / Ni) of the number of lithium atoms (Li) to the number of nickel atoms (Ni) in the resulting lithium mixture was 0.98. Except for the above, a positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1. The evaluation results are shown in Table 1. [Comparative Example 1] In the mixing step, the mixing ratio of lithium hydroxide monohydrate and nickel hydroxide was changed so that the ratio (Li / Ni) of the number of lithium atoms (Li) to the number of nickel atoms (Ni) in the resulting lithium mixture was 1.00. Except for the above, a positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1. The evaluation results are shown in Table 1. [Comparative Example 2] In the mixing step, the mixing ratio of lithium hydroxide monohydrate and nickel hydroxide was changed so that the ratio (Li / Ni) of the number of lithium atoms (Li) to the number of nickel atoms (Ni) in the resulting lithium mixture was 0.90. Except for the above, a positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1. The evaluation results are shown in Table 1. [Examples 3 and 4] A positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1, except that the gas supplied into the furnace during the firing step was a mixed gas of oxygen and air.
[0109] In Example 3, a mixed gas of 50% oxygen and 50% air by volume was used, so the oxygen concentration in the firing atmosphere was about 61% by volume.
[0110] In Example 4, a mixed gas of 70% oxygen and 30% air by volume was used, so the oxygen concentration in the firing atmosphere was about 76% by volume.
[0111] The evaluation results are shown in Table 1. [Comparative Example 3] A positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1, except that the atmosphere in the firing step was air and the firing temperature was 710°C.
[0112] As a result, the oxygen concentration in the firing atmosphere is approximately 21% by volume.
[0113] The evaluation results are shown in Table 1. [Examples 5 to 7] A positive electrode active material and a coin-type battery were produced and evaluated under the same conditions as in Example 1, except that the baking temperature in the baking step was changed.
[0114] The firing temperature was 630°C in Example 5, 680°C in Example 6, and 700°C in Example 7.
[0115] The evaluation results are shown in Table 1.
[0116] [Table 1] (Evaluation Results)
[0117] According to Table 1, it was confirmed that Examples 1 to 7, in which the ratio of elements other than Li in the Li site (3b site) was 2% or more and 8% or less and the contained lithium transition metal composite oxide was a positive electrode active material represented by the above-mentioned general formula (1), had a higher capacity retention rate than Comparative Examples 1 to 3. In other words, it was confirmed that the positive electrode active materials of Examples 1 to 7, when used in a lithium ion secondary battery, could improve cycle characteristics compared to the positive electrode active materials of Comparative Examples 1 to 3. [Explanation of symbols]
[0118] 10 Flow S1 Mixing process S2 firing process
Claims
1. A positive electrode active material for a lithium ion secondary battery, comprising secondary particles in which a plurality of primary particles are aggregated together, The lithium transition metal composite oxide has a layered rock salt structure, In the crystal structure of the lithium transition metal composite oxide, the ratio of elements other than Li to the Li site (3b site) is 2% or more and 8% or less, The lithium transition metal composite oxide has a composition represented by the following general formula (1): General formula (1): Li 1-x NiO 2+α (where 0.02≦x≦0.08, −0.1≦α≦0.1)
2. 2. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein the average particle size of the primary particles is 20 nm or more and 250 nm or less.
3. a mixing step of mixing a nickel compound, which is at least one type selected from nickel hydroxide and nickel oxide, with a lithium compound so that the ratio of the number of lithium atoms to the number of nickel atoms in the resulting lithium mixture is 0.92 or more and 0.98 or less; and a calcination step of increasing the temperature of the lithium mixture at a rate of 2° C. / min or less and calcining the mixture at a temperature of 600° C. or more and 700° C. or less.
4. The battery includes at least a positive electrode, a negative electrode, and a non-aqueous electrolyte; A lithium ion secondary battery, wherein the positive electrode comprises the positive electrode active material for lithium ion secondary batteries according to claim 1 or 2.
Citation Information
Patent Citations
Lithium transition metal oxide compound for lithium secondary battery positive electrode active material, its manufacturing method and secondary battery using it
JP2001243949A
Cathode active substance for nonaqueous secondary battery and cathode
JP2004355824A
Method for manufacturing positive electrode active material for nonaqueous electrolyte secondary battery
JP2017188444A
Positive electrode active material for nonaqueous electrolyte secondary battery
JP2017188445A
Nonaqueous electrolyte secondary battery
WO2017169129A1